Pembuatan Pupuk Organik Dari Limbah Tandan Kosong Kelapa Sawit - Warsito, Joko; Sabang, Sri Mulyani; Mustapa, Kasmudin (Universitas Tadulako, 2016)
The study’s aim is to utilize waste oil palm empty bunches into organic fertilizer and analyze the levels of nitrogen (N) and phosphorus (P). The methods used may include sampling and laboratory analysis. To determine the levels of nitrogen (N) and phosphorus (P) on the organic fertilizer from TKKS waste, spectrodirect was used. Based on analysis, it was obtained that level of nitrogen (N) is 2.033% and phosphorus (P) was 0.107%, while the amount of moisture content was 47.53% and ash content was 36,66%. Based on the SNI about compost quality from organic waste, the results of this study indicate that waste TKKS can be used as raw material for organic fertilizer.